Health security across the spectrum: Exploring the impact of socioeconomic factors on health insurance uptake in India - Madhubrota Chatterjee; Alok Aditya; Prashant Kumar Choudhary (Aging and Health Research, 2025)
Background: To ensure that healthcare services are accessible, health insurance is receiving increased amounts of attention in debates among health experts. The current disease pattern has increased the need for people to rely on intensive care, increasing both the cost of treatment and the frequency of accessing healthcare facilities. This paper aimed to examine the demographic, socio-economic, and health-related determinants of the choice to be insured with various types of health insurance schemes among older people in India. Methods: We used data from the Longitudinal Ageing Study in India (LASI) Wave-1, 2017–2018, comprising individuals aged 45 years and above. Multinomial Logistic Regression was employed to examine the association between the socio-demographic, socio-economic, and health status of respondents and their choice of opting for different types of health insurance. Results: The findings revealed that adults with multimorbid conditions were more likely to choose private insurance (RRR = 1.477, p < 0.01), while those currently working showed a higher preference for employer-based coverage (RRR = 2.184, p < 0.01). Individuals from poorer households were more inclined towards government insurance (RRR = 1.565, p < 0.01). Furthermore, higher education and urban residence increased the likelihood of employer and private insurance, while caste and regional differences reflected disparities in access and preference. Conclusion: The findings indicated that health and economic conditions play a central role in shaping health insurance choices in India. It highlighted the importance of responsive and inclusive health policies that must address both medical needs and financial vulnerability in the ageing population.